2003
DOI: 10.1136/gut.52.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Durability of HBeAg seroconversion following antiviral therapy for chronic hepatitis B: relation to type of therapy and pretreatment serum hepatitis B virus DNA and alanine aminotransferase

Abstract: Background and aims: Interferon (IFN) induced hepatitis B e antigen (HBeAg) seroconversion is durable in 80-90% of chronic hepatitis B patients. Preliminary reports on the durability of HBeAg seroconversion following lamivudine are contradictory. We investigated the durability of response following IFN, lamivudine, or IFN-lamivudine combination therapy in a meta-analysis of individual patient data. Patients and methods: Twenty four centres included 130 patients in total with an HBeAg seroconversion (HBeAg nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
3
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 32 publications
2
99
3
3
Order By: Relevance
“…Since both these parameters are linked with the extent of liver disease activity in the immune competent HBV carrier, our results further support the hypothesis that the extent of necrosis and inflammation influence LS significantly [20,[22][23][24] . Accordingly, in the 83 untreated patients without cirrhosis, multivariate analysis showed that intra-hepatic necrosis and inflammation scores and ALT values were the only factors influencing FS (P = 0.035 and P < 0.001 respectively), in addition to the stage of liver disease.…”
Section: Discussionsupporting
confidence: 84%
“…Since both these parameters are linked with the extent of liver disease activity in the immune competent HBV carrier, our results further support the hypothesis that the extent of necrosis and inflammation influence LS significantly [20,[22][23][24] . Accordingly, in the 83 untreated patients without cirrhosis, multivariate analysis showed that intra-hepatic necrosis and inflammation scores and ALT values were the only factors influencing FS (P = 0.035 and P < 0.001 respectively), in addition to the stage of liver disease.…”
Section: Discussionsupporting
confidence: 84%
“…6,7,31 Our data suggest that genotype C HBV infection may be responsible for the higher relapse rate in Asians, particularly Korean patients. 7,31 In the univariate analysis, our relapsers had a shorter duration of lamivudine therapy (9 vs. 13 months, respectively; P ϭ .041) and shorter additional therapy after HBeAg seroconversion (3 vs. 4.5, respectively; P ϭ .035). In addition, our patients with lamivudine therapy Ͻ12 months tend to have a higher relapse rate (57% vs. 37%, respectively), although the difference was only marginally significant.…”
Section: Discussionmentioning
confidence: 68%
“…A recent international study involving 59 patients treated with lamivudine (including 39 Korean patients) showed that high pretreatment HBV DNA and low pretherapy ALT were independent predictive factors of posttreatment HBeAg relapse. 31 In contrast, Dienstag et al 6 followed 40 patients (only 5 were Asians) for a median of 36.6 (4.8-45.6 months) months and found that low pretherapy ALT level was the only predictor for durable HBeAg response but at a marginally significant level (P ϭ .0724). The present study also showed that the median pretreatment levels of ALT were significantly lower in patients with durable HBeAg response (344 vs. 478 U/L, respectively; P ϭ .010).…”
Section: Discussionmentioning
confidence: 97%
“…If the sustained response for NA is assessed, a longer period of observation after drug withdrawal is necessary, as relapse can occur after the first year postreatment. 16 ers (loss of HBeAg 6 months postreatment) remained HBeAg-negative, whereas 58% of the initial responders presented levels of HBV-DNA < 2,000 UI/mL, three years after treatment. 30 Similarly, in a study conducted in Hong Kong, 46% of the initial responders remained HBeAg-negative and 29% presented levels of HBV-DNA < 5,000 UI/mL, three years after treatment.…”
Section: Sustained Response Versus Maintained Responsementioning
confidence: 97%
“…[12][13][14] Most hepatitis flares, after HBeAg seroconversion occur within six months after interferon therapy withdrawal, but can occur later, and even a few years after lamivudine withdrawal. 15,16 As a consequence, seroconversion of HBeAg can be used as a response marker only when sustained for at least six months after the end of therapy, and may be the best marker for treatment with pegylated interferon compared to NA.…”
Section: Seroconversion Of Antigen E Of Hepatitis B Virus (Hbeag)mentioning
confidence: 99%